Turkish Foreign Policy and the Role of the TGNA: Cases of Syria (and Iraq) Motions. Issue 1 (February 2019) - Esentürk, N. Nevra
The study aims to explore the role of the Turkish Grand National Assembly (TGNA) in Turkish foreign policy with respect to the cases of the Syria (and Iraq) motions. In the academic literature, there is considerable research arguing that parliaments do not influence parliamentary democracies' foreign policies. However, the existing literature does not provide examples or case studies that go beyond the limited role of legislatures in the foreign policies of parliamentary democracies. Parliaments, as the primary institutions for representative and participatory democracy, have limited but complementary role(s) in foreign policy, even under the circumstances where it is least likely for the parliaments to have influence on foreign policy affairs. Turkey's decisions on the Syria (and Iraq) motions illustrate how parliament can play complementary roles in foreign affairs, which is significant in the effective functioning of the foreign policy decision. What are the specific effects of the complementary role of the parliament? What is the position of the political opposition, intraparty dynamics, and public opinion in the parliament's playing that role? To elaborate on these questions, primary data are gathered from the proceedings of the TGNA during plenary sessions (covering the 24th, 25th, and 26th parliaments) to examine the deliberations and positions of political parties voting on the motions. In addition, the domestic context in the related terms is examined, elaborating on the state of political parties in the TGNA, single party, and intraparty dynamics. The primary data are supported by interviews. The findings of the study give significant insights that go beyond the limited role of parliaments in foreign policy and explore the complementary role of the legislature in foreign policy in terms of parliamentary legitimacy and the parliament as a venue for the opposition.